2019
DOI: 10.1111/tri.13432
|View full text |Cite
|
Sign up to set email alerts
|

Emerging technologies in organ preservation, tissue engineering and regenerative medicine: a blessing or curse for transplantation?

Abstract: Summary Since the beginning of transplant medicine in the 1950s, advances in surgical technique and immunosuppressive therapy have created the success story of modern organ transplantation. However, today more than ever, we are facing a huge discrepancy between organ supply and demand, limiting the potential for transplantation to save and improve the lives of millions. To address the current limitations and shortcomings, a variety of emerging new technologies focusing on either maximizing the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 157 publications
(194 reference statements)
0
21
0
Order By: Relevance
“…The utility of liver cell types is hampered by the overarching shortage of primary material, as high quality liver tissue is ear-marked for transplantation purposes where possible, leaving less optimal samples for research use. This is compounded by recent advances, which have increased the pool of viable tissue for transplantation ( 60 , 61 ). Further difficulties in using, or even benchmarking to, primary cells include the rapid loss of function of hepatocytes and other hepatic cell types during in vitro culture, particularly in monolayer ( 58 , 62 ), as well as limited proliferation potential of HSCs, combined with loss of their quiescent state in vitro ( 63 , 64 ).…”
Section: Mainmentioning
confidence: 99%
“…The utility of liver cell types is hampered by the overarching shortage of primary material, as high quality liver tissue is ear-marked for transplantation purposes where possible, leaving less optimal samples for research use. This is compounded by recent advances, which have increased the pool of viable tissue for transplantation ( 60 , 61 ). Further difficulties in using, or even benchmarking to, primary cells include the rapid loss of function of hepatocytes and other hepatic cell types during in vitro culture, particularly in monolayer ( 58 , 62 ), as well as limited proliferation potential of HSCs, combined with loss of their quiescent state in vitro ( 63 , 64 ).…”
Section: Mainmentioning
confidence: 99%
“…101 Grafts can be preserved under a variety of a perfusion temperatures; these include hypothermic (0°C-12°C), mid-thermic (13°C-24°C), sub-normothermic (25°C-34°C), and normothermic (35°C-38°C) conditions. 102,103 Studies on both small and large animal VCA models have demonstrated successful preservation of graft tissue for up to 24 h using machine perfusion. [104][105][106] In 2017, Werner et al 107 applied sub-normothermic machine perfusion to preserve human limbs for 24 h with a plasma-based perfusate.…”
Section: Machine Perfusionmentioning
confidence: 99%
“…The de-and recellularization technique has been used to produce heart, lung, liver, kidney, and intestine. Despite of some laboratory success, the technique seems to be improved before clinical application [27].…”
Section: Future Prospects 51 Organ Bioengineering and Regenerative Mmentioning
confidence: 99%